Research and development of thulium-doped fibre lasers - Morris, Daniel (My University, 2017)
Three thulium-doped fibre lasers (TDFLs) were developed: a large mode area (LMA) 25/400 “test” TDFL, a high power cw TDFL, and a Q-switched TDFL. For the test TDFL, the relationship between self-pulsing in TDFLs and laser reabsorption effects were explored by way of spectral and temporal measurements. Laser design aspects and technical procedures were also investigated. The highly efficient, high power cw TDFL produced a pump limited output power of 63 W with a slope efficiency of ~56 %. Thermal management schemes including splicing and fibre cooling were discussed and implemented. A polarisation maintaining thulium-doped fibre (TDF) was implemented for the Q-switched TDFL which produced pulse lengths of ~207 ns and peak powers of 1.17 kW at ~23 W of average laser output power. Gain switching of the Q-switched TDFL pump diodes further reduced the output pulse length to ~163 ns with peak powers of 1.35 kW.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree Master of Science, 2017
Keywords: Thulium